Inhibited expression of amylases and cellulases in crabs with hepatopancreatic necrosis disease and their regulation by EcR and HR38 - Ren, Qian; Zhao, Yuqi; Ma, Xingkong; Ge, Jiachun; Huang, Xin (Frontiers in Marine Science, 2023)
Hepatopancreatic necrosis disease (HPND) is a serious threat to the stable and sustainable development of the Chinese mitten crab farming industry. Studies have found that the hepatopancreas is the main lesion organ in HPND crabs, capable of causing metabolic abnormalities and non-feeding (starvation state). Here, four amylases (named as EsAmy1-4) and four cellulases (endo-beta-1, 4-glucanase, named as EsGlu1-4) that relate to carbohydrate metabolism were cloned from Eriocheir sinensis. Our studies found that the expressions of EsAmy1-4 and EsGlu1-4 were significantly decreased in the hepatopancreas of crabs with HPND. Moreover, the expressions of two important regulatory factors of carbohydrate metabolism, hormone receptor 38 (EsHR38) and ecdysone receptor (EsEcR), were remarkably decreased in the hepatopancreas of crabs with HPND. Further studies found that knockdown of EsHR38 and EsEcR could down-regulated the expressions of EsAmy1-4 and EsGlu1-4. In addition, downregulation of EsEcR could decrease the expression of EsHR38. Hence, HPND causes down-regulation of EsEcR expression, inhibits the transcription of EsHR38, further inhibits the expression of EsAmy1-4 and EsGlu1-4, and then leads to the abnormal carbohydrate metabolism. The abnormalities of carbohydrate metabolism may result in the abnormal food intake in crabs. This study provides new evidence for further understanding the mechanism of HPND.